2020
DOI: 10.1136/tobaccocontrol-2019-055306
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence smokers’ and ex-smokers’ use of IQOS: a qualitative study of IQOS users and ex-users in the UK

Abstract: BackgroundOne of the most widely available heated tobacco products is IQOS by Philip Morris International. However, there is a lack of independent research exploring IQOS initiation and subsequent use among smokers and ex-smokers.AimsTo (1) explore the reasons why smokers and ex-smokers use and continue/discontinue IQOS and (2) consider implications for future research and policy.ParticipantsAdult (18+) current (n=22) and ex-users (n=8) of IQOS who either currently smoked or quit smoking in the last 2 years.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 22 publications
4
60
0
1
Order By: Relevance
“…For example, smokers are more likely to switch to or initiate use of other alternative nicotine products (e.g., e-cigarettes) if they believe them to be less harmful than cigarettes [21][22][23]; however, few studies have addressed this for HTPs. A recent qualitative study of current and former IQOS users in the United Kingdom found that one of the main reasons for initiating HTP use and continued use was because it is 'less harmful', 'less hazardous', and 'less damaging' for their health than cigarettes [24]. A cross-sectional online survey of HTP users from various countries, mainly from Switzerland, reported 89% of respondents were using HTPs because they are less toxic than cigarettes [25].…”
Section: Discussionmentioning
confidence: 99%
“…For example, smokers are more likely to switch to or initiate use of other alternative nicotine products (e.g., e-cigarettes) if they believe them to be less harmful than cigarettes [21][22][23]; however, few studies have addressed this for HTPs. A recent qualitative study of current and former IQOS users in the United Kingdom found that one of the main reasons for initiating HTP use and continued use was because it is 'less harmful', 'less hazardous', and 'less damaging' for their health than cigarettes [24]. A cross-sectional online survey of HTP users from various countries, mainly from Switzerland, reported 89% of respondents were using HTPs because they are less toxic than cigarettes [25].…”
Section: Discussionmentioning
confidence: 99%
“…health, financial, physical, practical, psychological, and social factors. 43) Factors such as packaging, labeling, risk communication, price, and smoke-free policies appeared to influence initiation and use.…”
Section: Characteristics Of Heated Tobacco Product Usersmentioning
confidence: 99%
“…Moreover, HTPs' unique marketing strategy [39,40] and the similarity between HTPs and cigarettes [32] might be contributing factors to this difference. The products similarity makes it easier for users to switch between two products, and if HTPs deliver a certain better experience (such as cleaner and less smell) [41], then switching can occur for reasons other than health concerns.…”
Section: Characteristics Of Subgroups Of Concurrent Cigarette-htp Usersmentioning
confidence: 99%